Aproximación a un plan de negocios para la exportación de papa a la francesa congelada hacia Noruega (2020)
This project allows us to describe an approach to a French potato export business plan to Norway, due to the large importation of potatoes carried out by that country, and taking into account the ease of production and transformation of the raw material in our country. For the optimal development of this project, financial aspects will be analyzed, such as commercial strategies for product positioning in foreign territory, taking into account the production of national potatoes. In this way it was possible to demonstrate the potential according to the consumption made by Norway of the product. Make an export strategy and implement the incoterm ex - work, which allows the importer to modify the configuration at the manufacturing point, thus reducing transport costs and sending the route to the destination country. Likewise, the Neil Borden model “the concept of the marketing mix” was implemented, which allows such a clear and efficient export strategy to be carried out, through 4 fundamental elements: product, price, promotion and place.